2022
DOI: 10.1177/09697330221140512
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress, moral courage, and career identity among nurses: A cross-sectional study

Abstract: Background The concept of career identity is integral to nursing practices and forms the basis of the nursing professions. Positive career identity is essential for providing high-quality care, optimizing patient outcomes, and enhancing the retention of health professionals. Therefore, there is a need to explore potential influencing variables, thereby developing effective interventions to improve career identity. Objectives To investigate the relationship between moral distress, moral courage, and career iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, acting honourably, that is, following one's ideals and convictions, is not always easy (Hauhio et al., 2021 ). Recent changes in attitudes and underlying philosophies have influenced nursing (Peng et al., 2023 ). Oncology nursing involves numerous situations related to ethical issues, since a nurse is a person with whom the patient has the most contact during hospitalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, acting honourably, that is, following one's ideals and convictions, is not always easy (Hauhio et al., 2021 ). Recent changes in attitudes and underlying philosophies have influenced nursing (Peng et al., 2023 ). Oncology nursing involves numerous situations related to ethical issues, since a nurse is a person with whom the patient has the most contact during hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Moral courage plays a critical role in holistic nursing and varies across regions and populations. A variety of studies have explored the relationship between moral courage, moral sensitivity and moral distress among nurses who care for patients with various kinds of diagnoses (Konings et al., 2022 ; Pakizekho & Barkhordari‐Sharifabad, 2022 ; Peng et al., 2023 ), nursing students (Escolar‐Chua, 2018 ; Gibson et al., 2020 ; Huang et al., 2023 ; Koskinen et al., 2021 ; Mohammadi et al., 2022 ), psychiatric nurses (Jiao et al., 2022 ) and intensive care unit (ICU) nurses (Giannetta et al., 2022 ; Goktas et al., 2023 ; Zhang et al., 2023 ). These studies showed a positive correlation between moral courage and moral sensitivity, and a negative correlation between moral courage and moral distress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that moral courage is related to increased quality of care, 24 patient safety, 25 and career identity. 26 There is also a positive correlation between moral courage and social responsibility. 27 Therefore, it is essential to understand disaster relief nurses' sense of social responsibility to safeguard patients' rights and interests.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that moral courage is related to increased quality of care, 24 patient safety, 25 and career identity. 26 There is also a positive correlation between moral courage and social responsibility. 27…”
Section: Introductionmentioning
confidence: 99%
“…The undiscovered and unresolved moral distress will inevitably bring a series of negative consequences to professional nurses 12 . Studies have showed that moral distress is associated with increased stress, workplace fatigue, impaired professional relationships, job burnout, and poor professional identity, which can ultimately lead to an increased resignation rate of professional nurse [13][14][15] . In addition, under the negative impact of moral distress, professional nurses may unintentionally reduce their support for patients due to insu cient attention to patient's suffering and avoidance of certain patient demands or needs, thereby affecting health outcomes 16 .…”
Section: Introductionmentioning
confidence: 99%